The Discovery of Jan Chryzostom Pasek’s Romantic Manuscript (1821). The Third Beginning of Polish Romanticism - Szczeglacka-Pawłowska, Ewa (Colloquia Litteraria, 2018)
Jan Chryzostom Pasek’s seventeenth-century Pamiętniki [Diaries] has to be regarded an important manuscript for Polish Romanticism. The significance of this text can only be rivalled by Macpherson’s songs of Ossian, the Dvůr Králové Manuscript, or the Poetic Edda, which is attested by a considerable number of editions of this Old-Polish ‘epic work’. The first printing of a substantial part of the text appeared in 1821 in Warsaw in the Astrea magazine. This publication contributed to the complex phenomenon of the Romantic turning point. Pasek’s Pamiętniki should be counted as the third beginning of Polish Romanticism, after Adam Mickiewicz’s Ballady i romanse (first volume of Mickiewicz’s Poezyje) and Antoni Malczewski’s Maria.